Can being away from mobile phones for one hour benefit Muslim adolescents? The role of intervention program - Janon, Nazariah Shar'ie; Alwi, Azlin (2014)
Adolescence is a transition period from childhood to adulthood. During this period, adolescents experience rapid and marked physical, cognitive, emotional and social changes. As a result of these changes, often, they become restless and have conflicts with family members, at school and with peers. This paper aims to study whether giving one hour of intervention would be an effective way for adolescents to solve their conflicts. This investigation is important because through observation, adolescents who have conflicts, tend to run away from it by engaging with media, including computers, television and mobile phones. Through this study, the researchers tried to examine whether one hour of psychosocial intervention conducted after school is effective in helping adolescents to increase skills and knowledge to deal with the conflicts. It is hypothesized that students who participate in the program score higher in resilience and family social interaction measures than students in the control group who do not participate in the intervention. To test the hypothesis, 31 form four students were randomly assigned to either the experimental (n=16) or control (n= 15) group. Those who were in the experimental group received 10 intervention modules while those in the control group did not receive any intervention module. The results indicate that the scores for family social climate measures increased significantly after the intervention. Also, it was found that there is a significant difference in the post-test scores between the experimental and control groups. Thus, providing knowledge and skills to deal with the conflicts for at least one hour for ten consecutive weeks could help adolescents to develop resilience and positive interaction with family members. These findings are discussed in relation to current issues within the literature on psychosocial intervention and adolescence.